Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

(-y+5•3)+7.2y-9)=6.2y+n

Sagot :

(-y+5x3)+(7.2y-9)=6.2y+n
(-y+15)+(7.2y-9)=6.2y+n
since you're adding the two parentheses, you don't need to have them there
-y+15+7.2y-9=6.2y+n
7.2y-y +15-9 =6.2y+n
6.2y + 6 =6.2y+n
6.2y - 6.2y -n = -6
-n=-6
n=6